2021
DOI: 10.3390/ma14216252
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Blending Rice Husk Ash and Calcined Clay for the Production of Self-Compacting Concrete: A Review

Abstract: One principal approach to achieve self-compacting properties is the increased amount of finer constituents of the mixture. This, in turn, increases cement consumption leading to higher greenhouse gas emissions. Pozzolanic materials, like rice husk ash or calcined highly kaolinitic clays, have gained increased attention as supplementary cementitious materials in self-compacting concrete production. These materials could be viable alternative supplementary cementitious materials for sub-Saharan Africa which alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 139 publications
1
11
0
Order By: Relevance
“…The other mixes with RHA and 0.5% and 0.75% fiber obtained a "Tv" of 6.12 s and 6.65 s, respectively. This result is quite similar to the experimental outcomes by other researchers [27,40,43], who found that V-funnel flow times increase as the RHA and steel fiber are incorporated. According to them, EFNARC's specifications for fresh properties, including V-funnel flow duration and slump flow diameter, have been reached.…”
Section: Effect On V-funnel Flowsupporting
confidence: 91%
“…The other mixes with RHA and 0.5% and 0.75% fiber obtained a "Tv" of 6.12 s and 6.65 s, respectively. This result is quite similar to the experimental outcomes by other researchers [27,40,43], who found that V-funnel flow times increase as the RHA and steel fiber are incorporated. According to them, EFNARC's specifications for fresh properties, including V-funnel flow duration and slump flow diameter, have been reached.…”
Section: Effect On V-funnel Flowsupporting
confidence: 91%
“…According to this case, sustainable and greener production of construction technologies and eco-friendly evaluation of industrial by-products are current issues [ 35 ]. There have been lots of studies about the usage of industrial by-products as a replacement material against cement for the production of SCC [ 36 , 37 , 38 , 39 , 40 ]. This study is focused on the fine aggregate replacement effect on the fresh and hardened properties of SCC mixtures.…”
Section: Research Gapmentioning
confidence: 99%
“…CC are anhydrous aluminosilicate pozzolanic materials that can partially replace cement at high proportions and improve the strength and durability of concrete. Metakaolin is the most reactive CC in concrete and mortar due to its higher early strength compared to other CCs [ 18 , 19 , 20 ]. However, due to its frequent use in other competing industries, metakaolin is an expensive material and less available compared to the other 2:1 CCs.…”
Section: Introductionmentioning
confidence: 99%